RETRACTED: Mathematical modelling by using mental arithmetic as a method of teaching - Mamurov Bahodir; Akramova Gulbahor; Qo’ldoshev Rustambek; Jumaeva Feruza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001